Ventral Striatal Dopamine Synthesis Capacity Predicts Financial Extravagance in Parkinson’s Disease - Lawrence, Andrew D.; Brooks, David; Whone, Alan (Frontiers in Psychology, 2013)
Impulse control disorders (ICDs), including disordered gambling, can occur in a significant number of patients with Parkinson’s disease (PD) receiving dopaminergic therapy. The neurobiology underlying susceptibility to such problems is unclear, but risk likely results from an interaction between dopaminergic medication and a pre-existing trait vulnerability. Impulse control and addictive disorders form part of a broader psychopathological spectrum of disorders, which share a common underlying genetic vulnerability, referred to as externalizing. The broad externalizing risk factor is a continuously varying trait reflecting vulnerability to various impulse control problems, manifested at the overt level by disinhibitory symptoms and at the personality level by antecedent traits such as impulsivity and novelty/sensation seeking. Trait ‘disinhibition’ is thus a core endophenotype of ICDs, and a key target for neurobiological investigation. The ventral striatal dopamine system has been hypothesized to underlie individual variation in behavioural disinhibition. Here, we examined whether individual differences in ventral striatal dopamine synthesis capacity predicted individual variation in disinhibitory temperament traits in individuals with PD. Eighteen early-stage male PD patients underwent 6-[18F]Fluoro-L-DOPA (FDOPA) positron emission tomography (PET) scanning to measure striatal dopamine synthesis capacity, and completed a measure of disinhibited personality. Consistent with our predictions, we found that levels of ventral, but not dorsal, striatal dopamine synthesis capacity predicted disinhibited personality, particularly a propensity for financial extravagance. Our results are consistent with recent preclinical models of vulnerability to behavioural disinhibition and addiction proneness, and provide novel insights into the neurobiology of potential vulnerability to impulse control problems in PD and other disorders.